If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3) + x + x = 130 Reorder the terms: (3 + x) + x + x = 130 Remove parenthesis around (3 + x) 3 + x + x + x = 130 Combine like terms: x + x = 2x 3 + 2x + x = 130 Combine like terms: 2x + x = 3x 3 + 3x = 130 Solving 3 + 3x = 130 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 3x = 130 + -3 Combine like terms: 3 + -3 = 0 0 + 3x = 130 + -3 3x = 130 + -3 Combine like terms: 130 + -3 = 127 3x = 127 Divide each side by '3'. x = 42.33333333 Simplifying x = 42.33333333
| (8x+8)(6x^2+6x+5)= | | 11/4x=4/3 | | (x+2)*(3x-6)=(x+1)*(3x-4) | | 2.3/x=5.2 | | x-(3x+4)=5-(4x+3) | | 10=3v-17 | | n-n=-4(2n-8)+8(n+12) | | 25=a(30-0)(30-60) | | x-56=64 | | -6+3(1-9v)=-24 | | x-32=28 | | 190+b=200b | | (x+5)*28=2x*21 | | 10x-22=8x+12 | | x*ln(x)=(ln(3))/3 | | (x+5)*28=2x+21 | | x^2+y^2-12x+4y=24 | | x+5*28=2x+21 | | s^2+20+4s= | | 4x=44p-16 | | 4m-30+m=3m+4 | | 3(-16+7x)-15x= | | 20*(20+x)=15*(15+3x) | | 6+17(-10-8g)= | | 2q-5=7q | | 75+2=15+5 | | 11-3x+6y=0 | | P(n)=3n | | 10a-7(-17a-13)= | | (x*x)=(x-2)*(x+2) | | 21+5=15+11 | | X*12=6*(x+4) |